Una base dati armonizzata per la mappatura europea di area e produzione delle colture a livello regionale (GEOmedia, 2024)
Agricultural production plays an important role in the global economy, contributing greatly to the supply of food resources and human well-being. Mapping the areas of agricultural coverage and calculating their respective average annual production values is useful for orienting food security strategies, in a context of climate change and a growing global population. Despite their importance, today no complete and updated maps exist for all types of crops. To provide this critical data lack, we have harmonized statistical datasets at a regional level of detail across Europe (EU-27) to develop a unified dataset consisting of the best available data in the context of agricultural monitoring activities carried out by the CREA. This document illustrates the methodologies adopted to create an harmonized database and an open and easy-to-use cartographic atlas of agricultural area and production, based on accessible, interoperable and reusable data available from Eurostat.The availability of detailed maps of area and crop production at a regional level can help optimize a wide range of agricultural monitoring, ranging from early warning on phytopathological conditions, to assessment of crop conditions, to production forecasts and the assessment of damage caused by extreme weather events, agricultural statistics, agricultural insurance and climate mitigation and adaptation actions.